An experimental and theoretical investigation of unstable Fischer chromium carbene complexes - Makanjee, Che Azad (Rhodes University, Faculty of Science, Department of Chemistry, 2013)
This organometallic study involves the use organostannanes and organolithiums as precursors to chromium Fischer carbene complexes. Fischer carbenes are typically electrophilic and are stabilized by a single Ï€-donor substituent, and contain low oxidation state metals (often but not always from Group 6). They are highly reactive and can give access to a range of biologically active compounds through cyclopropanations, insertions, coupling and photochemical reactions. Synthesis and characterization of three MOM-protected Î±-alkoxy organostannanes was successfully carried out via a nucleophilic addition of tributylstannyllithium to suitable aldehydes, and immediate protection of the alcohol with MOM. Two N-BOC protected Î±-amino organostannanes were successfully synthesized and characterized via Î±-lithiation and tin-lithium exchange in the presence of TMEDA. Tin-lithium transmetallation of the organostannanes allowed access to the organolithiums required for the synthesis of novel Fischer carbenes. Addition of chromium hexacarbonyl to the organolithiums formed the acylpentacarbonyl chromate salt which was alkylated with Meerwein salt, resulting in the Fischer carbene and a by-product, tetrabutyltin, which proved difficult to remove. Several Fischer carbenes were synthesized and characterized, some simple and known and some novel. In silico work explored the reaction coordinate of the [2+2] cycloaddition towards the formation of Î²-lactams, and the photoactivation cycle that precedes this process. Computational work also showed the effect of the ligand on the stability and reactivity of the carbene. It was found that in some cases the oxygen on the ligand could negatively influence the stability of the carbene (when compared to a simple methyl carbene). A link between bond orders and back donation in Fischer carbenes was explored in an attempt to theoretically predict the stability of a range of carbenes.,Microsoftï¿½ Office Word 2007
Keywords: Chromium; Organolithium compounds; Carbenes (Methylene compounds); Organometallic chemistry; Organometallic compounds; Organochromium compounds